2017
DOI: 10.1177/1363459317695630
|View full text |Cite
|
Sign up to set email alerts
|

How do health behaviour interventions take account of social context? A literature trend and co-citation analysis

Abstract: In recent years, health behaviour interventions have received a great deal of attention in both research and policy as a means of encouraging people to lead healthier lives. The emphasis of such interventions has varied over time, in terms of level of intervention (e.g. individual vs community) and drawing on different disciplinary perspectives. Recently, a number of critiques have focused on how health behaviour interventions sometimes sideline issues of social context, framing health as a matter of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…Critique has focused on reductionist perspectives that emphasise physiological effects and concomitantly presupposes knowledge (read: ignorance) and motivation (or lack thereof) determines health related behaviour. In this regard, EiM approaches reflect the findings of Holman et al (2017) who identified health behaviour interventions more broadly have largely failed to acknowledge the importance of cultural and social contexts. We outline the forces maintaining the status-quo before arguing both EiM proponents and critics would benefit from a change in approach.…”
Section: Physiological Rationale For Exercise As Medicine: Movement Imentioning
confidence: 99%
“…Critique has focused on reductionist perspectives that emphasise physiological effects and concomitantly presupposes knowledge (read: ignorance) and motivation (or lack thereof) determines health related behaviour. In this regard, EiM approaches reflect the findings of Holman et al (2017) who identified health behaviour interventions more broadly have largely failed to acknowledge the importance of cultural and social contexts. We outline the forces maintaining the status-quo before arguing both EiM proponents and critics would benefit from a change in approach.…”
Section: Physiological Rationale For Exercise As Medicine: Movement Imentioning
confidence: 99%
“…20 Another study published in 2017 found that references to social context had become less frequent in health behaviour change intervention research since 2006 and called on research funders and other stakeholders to develop guidance on how to take account of social and cultural contexts. 18,21 There is a need both to identify existing good practice and to move the field forward by extending existing perspectives and inviting new approaches that address the significance of context for population health interventions. This document seeks to pull together recent thinking and practical experience of addressing context within PHIR.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Critical histories of health psychology (Crawford, 2006;Murray, 2014) have argued that health psychologists need to take a role in addressing those social injustices that produce ill-health. Despite this, behaviour change interventions targeting social context have become rarer in the last decade (Holman, Lynch, & Reeves, 2017).…”
mentioning
confidence: 99%